Book review: Yogesh Snehi and Lallan S. Baghel (Eds.), Modernity and Changing Social Fabric of Punjab and Haryana. (April 2020) - Kaur, Manjit
Yogesh Snehi and Lallan S. Baghel (Eds.), Modernity and Changing Social Fabric of Punjab and Haryana . Delhi: Primus Books, 2018, 453 pp., ₹1, 295. ISBN: 978-93-86552-98-3.